Spółdzielnie w orzecznictwie Trybunału Konstytucyjnego - Stelina, Jakub (PRAWO i WIĘŹ, 2023)
In this article the author discusses the most important judgments of the Constitutional Tribunal in cases concerning cooperatives and cooperative law, issued since the beginning of the new Constitution of the Republic of Poland of 1997. In total, the Constitutional Tribunal has examined thirty-five such cases. As the Constitution does not contain regulations relating directly to cooperatives, hence these cases concerned the assessment of individual provisions of cooperative law with the fundamental civil rights guaranteed by the Basic Law. Examples include such rights as the right to association, the right to protection of property, or standards arising from the principle of a democratic state of law.